1998
DOI: 10.1128/jvi.72.3.2388-2397.1998
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Recombinant Capsid Proteins of Adenovirus in Humans: Antifiber and Anti-Penton Base Antibodies Have a Synergistic Effect on Neutralizing Activity

Abstract: Replication-deficient adenovirus used in humans for gene therapy induces a strong immune response to the vector, resulting in transient recombinant protein expression and the blocking of gene transfer upon a second administration. Therefore, in this study we examined in detail the capsid-specific humoral immune response in sera of patients with lung cancer who had been given one dose of a replication-defective adenovirus. We analyzed the immune response to the three major components of the viral capsid, hexon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…15,16 Depletion of Ab against the three main Ad capsid proteins (fiber, penton, hexon) by affinity chromatography in Ad immune serum, greatly reduces the inhibitory effect of these sera on vaccine vector efficacy, as demonstrated by an almost complete restoration of transgene expression level. 15 Although nAbs targeting the main 3 capsid proteins have been detected in vitro, 15,[17][18][19] they do not equally contribute to Ad vector neutralization in vivo. The relative contribution of each subset of nAbs has been teased apart by vaccinating Ad preimmuned animals with capsid chimeric Ad vectors.…”
Section: Humoral Responsesmentioning
confidence: 99%
“…15,16 Depletion of Ab against the three main Ad capsid proteins (fiber, penton, hexon) by affinity chromatography in Ad immune serum, greatly reduces the inhibitory effect of these sera on vaccine vector efficacy, as demonstrated by an almost complete restoration of transgene expression level. 15 Although nAbs targeting the main 3 capsid proteins have been detected in vitro, 15,[17][18][19] they do not equally contribute to Ad vector neutralization in vivo. The relative contribution of each subset of nAbs has been teased apart by vaccinating Ad preimmuned animals with capsid chimeric Ad vectors.…”
Section: Humoral Responsesmentioning
confidence: 99%
“…In addition to Ad-specific T cells, Ad-specific neutralizing antibodies (NAbs), predominately directed against hexon, fiber and penton base, are generated following the first exposure to Ad, whether naturally occurring or after one immunization with an Ad vector [51,91,92]. These NAbs inhibit Ad transduction of cells by a variety of methods, including prevention of cell attachment or facilitation of virus aggregation and clearance [51].…”
Section: Humoral Adaptive Immune Responsesmentioning
confidence: 99%
“…Further studies indicated that HD-Ad vectors delivered systemically induce early, capsid-dependent inflammatory cytokines similar to those induced by Ad5 vectors, although the induced cytokine release is short-lived in comparison and adaptive immune responses are not induced [154]. The discovery that the majority of anti-Ad immune responses are produced against capsid proteins further emphasizes that, similar to unmodified Ad vectors, systemically delivered HD-Ad vectors must evade capsid-specific PEI to provide optimal efficacy in humans [51,81,82,91,92].…”
Section: Helper-dependent Adenovirusesmentioning
confidence: 99%
“…The humoral immune response to HAdVs consists of both neutralizing and nonneutralizing antibodies. 20 Although the anti-HAdV-neutralizing antibodies (nAbs) targeting the three major capsid proteins, hexon, penton, and fiber, have been confirmed, 21,22 the anti-hexon nAbs are the most significant in vector neutralization. The major epitopes for anti-hexon nAbs are located in the exposed loops, also known as hypervariable regions, located on the surface of the virus particle.…”
Section: Preexisting Adenovirus Immunitymentioning
confidence: 99%